2020
DOI: 10.4049/jimmunol.2000689
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Peptides Elicit Distinct CD8+ T Cell Responses following Influenza A Virus Infection

Abstract: The presentation of pathogen-derived peptides on MHC class I molecules is essential for the initiation of adaptive CD8+ T cell immunity, which in turn is critical for effective control of many significant human infections. The identification of immunogenic pathogen-derived epitopes and a detailed understanding of how they are recognized by TCRs is essential for the design of effective T cell–based vaccines. In this study, we have characterized the T cell recognition and immune responses in mice to two naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…While some literature discusses subsets of this compartment, which include various sub populations, including some that have been referred to as atypical naïve–like memory/effector cells [ 6 ], the vast majority of these cells are naïve. Some recent works show that the unique TCR reactivity to immunogenic pathogen-derived epitopes is present already in the naíve repertoire prior to immune expansion in B6 mice [ 7 ] and that Naïve T cells can manifest shifting to Teffs, which can effectively kill tumor cells [ 8 ]. Interestingly, recent evidence has shown that CD4+ naive T cells significantly more heterogeneous than was previously thought, and that these sub populations of T cells are diverse in phenotypes, differentiation stages, persistence, functions, and anatomic localizations [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…While some literature discusses subsets of this compartment, which include various sub populations, including some that have been referred to as atypical naïve–like memory/effector cells [ 6 ], the vast majority of these cells are naïve. Some recent works show that the unique TCR reactivity to immunogenic pathogen-derived epitopes is present already in the naíve repertoire prior to immune expansion in B6 mice [ 7 ] and that Naïve T cells can manifest shifting to Teffs, which can effectively kill tumor cells [ 8 ]. Interestingly, recent evidence has shown that CD4+ naive T cells significantly more heterogeneous than was previously thought, and that these sub populations of T cells are diverse in phenotypes, differentiation stages, persistence, functions, and anatomic localizations [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…This might lead to crossrecognition of multiple antigenic peptides, thereby increasing the immunological overlap between self and non-self antigens. The immunological relevance of CD8 + TCRab cross-reactivity is still a matter of debate (60)(61)(62)(63), although seminal studies on potential cross-reactivity of T1D-relevant CD8 + T cell clones for T1D-associated human antigens and pathogens have already been published (28,64,65). In future analyses of cis-spliced epitope candidates, including TCR degeneracy would represent a computational challenge, although it might significantly increase the number of viral-human zwitter epitope candidates potentially associated to T1D.…”
Section: Discussionmentioning
confidence: 99%
“…Current research and development strategies of universal influenza vaccines are designed to protect against a wide range of pathogens [ 154 , 155 ]. Universal influenza vaccine is mainly based on cross-protective T cell response [ 156 , 157 ], and its adjuvants and vaccination methods [ 158 ] have also been studied. All of these strategies could be explored for COVID-19 vaccine development Neutralizing antibodies induced by vaccines are not the only mechanism of protection.…”
Section: Effective Vaccination Strategies Against Future Sars-cov-2 V...mentioning
confidence: 99%